PENERAPAN ANALISIS SWOT DALAM MENGEMBANGKAN USAHA INDUSTRI KERIPIK - Pangaribuan, Ferina Angela; Yance; Mardhiyah, Ainun (Journal Business Administration: Entrepreneurship and Creative Industry, 2022)
The country's economic growth is one of the important steps in analysing the nation's economic development. Therefore, it is necessary to formulate a strategy to grow the domestic industry as a requirement in increasing state revenues. One of the strategies carried out by the government is to grow Micro, Small and Medium Enterprises (MSMEs). UD. Rezeki Baru is one of the MSMEs engaged in snack food processing by managing sweet potatoes into chips under the brand name Cap Rumah Adat Minang. This study aims to determine the strategy of UD. Rezeki Baru in developing the sweet potato and banana chips industry business with the Minang Traditional House stamp and looking for the right alternative strategy in developing its business. The research method used is a descriptive method with a qualitative approach. Research data were obtained from observations, interviews and literature studies. The research informants were divided into three groups, namely key informants, main informants and additional informants determined by purposive sampling. Data analysis techniques are qualitative descriptive analysis and SWOT analysis. Based on the results of the study, it is known that UD. Rezeki Baru uses an intensive strategy in developing its business, developing existing products and expanding the market. The right alternative strategy recommendation is the W-T strategy, by maintaining strengths and taking advantage of existing opportunities, as well as minimising existing weaknesses and avoiding threats.